Digital Transformation of Stock Management with a Web-Based Inventory System Using the Extreme Programming Method (Case Study: PT.Tata Makmur Sejahtera) - Khaidar, Daffa Muhammad; Darmanto, Tedjo; Hermanto, Moch. Irwan (Media Jurnal Informatika, 2025)
PT Tata Makmur Sejahtera is a textile company that since 2004 has grown rapidly in services and number of branches. Currently, stock management still uses Microsoft Excel and manual spreadsheets, which risks causing data input errors and is less efficient. To overcome these problems, a web-based inventory management system was developed using the Extreme Programming method to improve the efficiency and accuracy of stock management. The system is designed to be responsive, easy to use, and allows direct user testing for iterative UI/UX improvements. Through this system, the company has the ability to manage stock more systematically, prevent shortages or excess goods, and increase the effectiveness of warehouse operations.